Business and Society: An Introduction - France Maphosa; Langtone Maunganidze (Palgrave Macmillan, Cham, 2022)
This chapter introduces the book by contextualizing it to the African context. It presents a brief discussion on corporate social responsibility in nine countries, namely Angola, Cameroon, Ghana, Kenya, Nigeria, South Africa, Zambia and Zimbabwe in order to provide a comparative perspective. The general picture emerging from the review of literature on corporate social responsibility in Africa is that it is not widely practised, mainly because of weak legislation. The chapter then focuses on Botswana, providing the rationale for Botswana being the focus. While it is widely acclaimed as Africa’s economic “miracle”, it has, at the same time, high levels of poverty, inequality and unemployment and high rates of HIV/AIDS prevalence. This makes this the examination of the role of business in society in Botswana imperative.